THE STRUGGLE OF GENDER EQUALITY IN FIVE NOVELS OF Nh. DINI - Nasution, Siti Norma; Kutha Ratna, I Nyoman; Weda Kusuma, I Nyoman (e-Journal of Linguistics, 2013)
This study explores the problems of women , patriarchal culture and the fight for gender equality as exposed in Nh. Dini’s novels. There are still many women who are trapped in domestic sector and loose their rights to manage their own lives with their own way. There have been many women who are successful working in public sector, but the number are still very small compared to the number of men who are successful. This study tends to expose the problems of women to reach gender equality for women. This study is importantly conducted because Nh. Dini’s literary works reveal the problems of women related to patriarchal culture which hampers the progress of women. The present study is different with the previous one, because this study explores feminism ideology which is against patriarchal culture and tradition which is still adopted by people as portrayed in five novels of Nh. Dini. The theory of Dinamic Structuralism is used to explain the interconnection of all aspects and components of the novels to get the complete meaning. The theory of Sociology of Literature is used to relate the social problems in the novels to the realities in the real world. The theory of Feminism is used to understand the novels related to women problems, patriarchal culture and gender equality. Text analysis based on the problems of the study revealed that many women are still trapped in domestic sector, still dominated by patriarchal culture. They loose their fundamental rights to manage their own lives and to improve their lives quality to become qualified women. Consenquently the women are so dependent on other people. Analysis about the factors which caused the poverty and misery of women revealed that the main cause of the women problems in the novels is patriarchal culture. The women are not permitted to work in public sector to earn their own lives. Consenquently many women become poor for being jobless. The fight for gender equality that revealed in five novels are in agreement with the thought of feminism ideology, among others is the fight to get education and job. Feminism ideology also fight to free women from patriarchal domination by living without marriage or claiming for divorce from the husband who can not protect their wives anymore.
Keywords: Women problems, patriarchal culture, gender equality, feminism ideology